The Development of Distributed Leadership in Lithuanian Pre-school Education Institutions - Dambrauskienė, Dalia; Liukinevičienė, Laima (Socialiniai tyrimai, 2018)
The article analyses the possibilities of distributed leadership development in Lithuanian pre-school education institutions. The aim of the article is to analyse the theoretical literature and other sources (strategic documents, legal acts, statistical information) and to reveal the possibilities of distributed leadership development in Lithuanian pre-school education institutions.Therefore, the following objectives have been set up: to provide the theoretical assumptions of distributed leadership and to analyse the interface between the development of distributed leadership and the context of Lithuanian pre-school education institutions.The article summarizes the scientific approach to distributed leadership. Attention is paid to the fact that the idea of distributed leadership is becoming popular, however, researchers use different definitions and concepts to define this leadership. These differences potentially arise from the different contexts where this form of leadership is analysed. Although there is no one common definition of distributed leadership, researchers identify some active participants (leaders) and emphasize the need for favourable environment (organizational culture) of mutual interaction. Distributed leadership in the organization is often characterized by the following features: each person’s professionalism and experience are appreciated and supported; community spirit and atmosphere of trust prevail; attention is paid to pupils’ learning experience; community members are continuously learning; everyone is included in decisionmaking; the management structures of the organization are (re)organized; leadership is carried out through (non) formal posts and actions; responsibility and accountability of all participants are important.Researchers acknowledge that distributed leadership is contextual, therefore, they believe that it is necessary to take into consideration the uniqueness of organizations. However, different researchers identify and analyse different contexts which, in their opinion, influence leadership in organizations. Some researchers identify the external and internal contexts of the organization, other researchers identify the institutional context, community context, national-cultural context, economic context, political context, school development context, and personal-specific context.After the comparison of the particularities of pre-school education institutions and general education schools, it is evident that the duration of work of these education institutions and the duration of work of teachers are different. These differences are significant, as distributed leadership is implemented through the interaction of leaders and their followers. Therefore, the more teachers and other employees are involved into the implementation of their direct responsibilities (education and/or care of children), the more it is complicated to find time for mutual interaction. In this respect, the pre-school education institutions are in less favourable situation in order to implement distributed leadership. The differences between pre-school and general education institutions are determined by different age of learners, different nature and intensity of communication with parents and the fact that pre-school education is non-formal education. Therefore, there is a bigger possibility to involve learners’ parents into the processes of distributed leadership in the institutions of pre-school education rather than in general education institutions.Differences not only between different types of education institutions (general education institutions and pre-school education institutions), but also between education institutions of the same type are partly determined by the Law on Local Self-Government of the Republic of Lithuania (1994), as different municipalities may have different organization and funding of pre-school education institutions, different criteria and procedures of external assessment of institutions. Differences between education institutions of the same type in the same municipality are also possible, as the education system in Lithuania is decentralized and education institutions implementing different educational programs have the possibility to make decisions on the management, curriculum content, and measures. The documents regulating the assessment of activity give considerable power to the communities of institutions, i.e. teachers, employees, learners’ parents. Therefore, it is possible to state that the institutional context is quite favourable for the development of distributed leadership in Lithuanian pre-school education institutions.According to the statistical data of Lithuania, there are significant disparities among the same type of education institutions in urban and rural areas, which are determined by different contexts of communities. Significant disparities are also observed among communities of different types of education institutions, which are partly determined by the different age and gender of the heads and teachers of education institutions.The studies of cultural dimensions carried out by researchers show that Lithuania is attributed to the countries with high power distance (strong social hierarchy), and this can cause difficulties to develop distributed leadership. Since the statistical sociodemographic data (age, gender, education) of Lithuanian education institutions are quite different from the general statistics of Lithuania, it is appropriate to carry out empirical studies that would assess the cultural dimensions of Lithuanian education institutions (preschool education and general education institutions) as well as power distance (i.e. social hierarchy).The context of the development of Lithuanian schools is favourable for the development of the ideas of distributed leadership both in general education and pre-school education institutions. The favourable context for the implementation of the ideas of leadership is determined by the Lithuanian strategic documents and strategic documents of education policy. Also, the project “Time for Leaders”, initiated by the Ministry of Education and Science and which has been implemented for almost a decade, plays a significant role in disseminating the ideas of leadership in Lithuania.According to the theoretical research, it is possible to state that the institutional, school development and personal-specific contexts of Lithuanian pre-school education institutions are favourable for the development of distributed leadership in pre-school education institutions. Meanwhile, the national cultural context, the different contexts of communities of education institutions can pose difficulties to implement the ideas of distributed leadership. The analysis of the theoretical material and legal framework reveals the need to carry out the empirical research of distributed leadership in Lithuanian pre-school education institutions, to reveal the challenges and particularities of its implementation, as well as to reveal good practices.
Keywords: pre-school education institution; distributed leadership; context